USING VR/AR TECHNOLOGIES IN THE PROCESS OF TEACHING PHYSICS - Ashirbekova S. U.; Eshbaeva M. (American Journals Publishing, 2023)
Aspects of the use of virtual and augmented reality technology in the school education system are considered. The advantages and limitations of using these technologies are given. Directions and examples of the use of virtual and augmented reality technologies in the educational environment are offered. When used correctly, these technologies can help create an effective modern educational environment, individualize the learning process, and expand learning opportunities.
Keywords: Innovative education, virtual reality, augmented reality, Virtual Reality, Augmented Reality, interface, VR platform, educational content.